2015
DOI: 10.1161/circimaging.115.003260
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Myocardial Function in Children With Pulmonary Hypertension

Abstract: Background Through ventricular interdependence, pulmonary hypertension (PH) induces left ventricular (LV) dysfunction. We hypothesized that LV strain/strain rate, surrogate measures of myocardial contractility, are reduced in pediatric PH and relate to invasive hemodynamics, right ventricular (RV) strain, and functional measures of PH. Methods and Results At two institutions, echocardiography was prospectively performed in 54 pediatric PH patients during cardiac catheterization, and in 54 matched controls. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 29 publications
5
53
1
Order By: Relevance
“…70,71 In total, 43 datasets of strain measures from 63 manuscripts of strain measures with 2325 children were considered eligible for assessment in the meta-analysis (Figure 2). 7-49 Forty out of 43 authors (93%) responded and provided either the raw strain data and/or filled in the missing information on study quality and potential sources of variability. The remaining three data sets (7%) from the authors that did not respond via electronic mail were included with the available information provided in their respective manuscripts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…70,71 In total, 43 datasets of strain measures from 63 manuscripts of strain measures with 2325 children were considered eligible for assessment in the meta-analysis (Figure 2). 7-49 Forty out of 43 authors (93%) responded and provided either the raw strain data and/or filled in the missing information on study quality and potential sources of variability. The remaining three data sets (7%) from the authors that did not respond via electronic mail were included with the available information provided in their respective manuscripts.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-one datasets with 2084 patients were eligible for the meta-analysis of GLS or LS ; 7-24,26-34,36-49 26 datasets with 1506 patients were eligible for the meta-analysis of GCS or CS , 7,9,11,12,14-20,23,25,26,28-31,33,34,41-44,46,48 and 15 datasets with 1092 patients were eligible for the meta-analysis of GRS or RS. 11,15,16,19,20,23,25,26,28,29,33,41-43,46 The patient characteristics of the included studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Nevertheless, over-reliance on a single echocardiographic variable and false estimation of RV systolic pressure because of poor CW-Doppler envelopes or severe tricuspid regurgitation can limit the value of the methodology for non-PH experts. 18 More novel, potentially prognostic echocardiographic variables to assess RV/LV geometry/ function and RVP or PAP in pediatric PH include RA size 19,20 ; tricuspid annular plane systolic excursion 21 ; RV outflow tract velocity time integral; trivial tricuspid/RVOT velocity time integral ratio 22 ; pulmonary regurgitation velocity; RV size 20 ; LV size, LV end-systolic eccentricity index, end-systolic and end-diastolic RV/LV ratio 23 ; RV stroke work 24 ; LV strain and strain rate 25 ; RV systolic/diastolic duration ratio 26 ; and pulmonary artery acceleration time (Koestenberger M, MD, unpublished data, 2016). A combination of the above variables can help the clinician avoid some of the pitfalls of the echocardiographic examination at initial diagnosis and serial…”
Section: See Article By Burkett Et Almentioning
confidence: 99%
“…A deformation imaging (speckle tracking) study on the identical cohort of pediatric PH patients had identified decreased systolic LV strain/strain rate, predominantly within the septum, with relationships to invasive hemodynamics, RV strain, and functional PH measures. 25 In the current study, 27 the authors aimed to study the impact of pulmonary hemodynamics and ventricular interdependence on LV diastolic function in pediatric PH. By doing so, they directed their focus beyond RV systolic dysfunction that is known to determine clinical outcome but often is a late finding, particularly in younger patients, and even in those with advanced PAH.…”
Section: Hansmann LV Diastolic Dysfunction In Pediatric Phmentioning
confidence: 99%